Religions that can be legally practised and professed in Malaysia / Siti Nabila Huda Zaidisham…[et al.] - Zaidisham, Siti Nabila Huda; Arazmi, Nur Aimi; Tingku Zahari, Tengku Najiha; Mohamed, Marini Aisyah (2009)
The vitality of religion in Malaysia has been acknowledged by the Constitution by referring to Article 11 in which freedom of religion has been included as part and parcel of Fundamental Liberties granted to all citizen of Malaysia including those residing in the country regardless of his citizenship and domicile. Furthermore, Article 3(1) acknowledges Islam as the Federation's religion and allows other religions to be practised in peace and harmony. Article 3 symbolises the sense of unity, tolerance and respect between religions. The emergence of new cults and new religious groups throughout the world became an issue when these religions were not accepted by Malaysians. Thus, it is vital to determine which religions can be practised by Malaysians without being punished. The aim of this research has led the researchers to analyse Article 3 and Article 11 of the Constitution in depth regarding the religions that can be legally practised and professed in Malaysia and to come out with suggestions for appropriate incorporation to be made into the Constitution regarding religions that can be legally professed and practised besides making suggestions on what are the elements in order to infer a religion is an established religion. It is hoped that the research will provide better understanding and awareness regarding the religions that can be legally practised and professed in Malaysia and the rights to freedom of religion granted by the Constitution.